PLANNING AND IMPLEMENTING TOTAL QUALITY MANAGEMENT IN EDUCATION: THE CASE OF CYPRUS - Christos Karageorgos; Athanasios Kriemadis; Antonios Travlos; Dimitrios Kokaridas (Universitas Ahmad Dahlan, 2021)
The transition of TQM from the business field in education started in 1994 to strengthen the humanistic nature of education and improve quality service with the full participation of all involved. Cyprus recognized as a country with highly developed education services and qualitative characteristics that are easily identifiable. However, no studies are published yet concerning the implementation of TQM in Cyprus. The purpose is to examine the design and implementation of TQM at primary and secondary school settings in Cyprus and create a reference point of collecting all partial findings of TQM implementation in Cypriot education. A systematic recording of research included the design and implementation of TQM in education settings using ten electronic databases and keywords including education, TQM and the six factors determining the quality of TQM services. The research included peer-reviewed articles, doctoral theses, and conference abstracts during the last 20 years, leading to future TQM implementation conclusions. Cyprus nowadays focuses on the overall evaluation and implementation of TQM through innovation and quality improvement in education, differentiated and virtual teaching, adapted learning and inclusion of students with disabilities, and hiring new teaching staff that will implement a holistic approach of promoting TQM within school settings.